To Assess and Evaluate the Characterisation of Gelatin as A Material of Choice for Membrane Adhesive - Ramesh, Kausthuba; Rohinikumar, Subhashree; Nesappan, Thiyaneswaran (Journal of Neonatal Surgery, 2025)
The current study aims to develop a novel tissue adhesive glue incorporating synthetic and semisynthetic material. The tissue glue is fabricated by incorporating bisphenol A-glycidyl methacrylate (Bis-GMA), gelatin methacrylate and methacrylic acid. The tissue adhesive was then tested for compressive strength, swelling behaviour and compatibility. The fabricated tissue adhesive exhibited compressive strength of 16.14 MPa and swelling behavior 3.69% at 3 hours. The biocompatibility of the material was 85.3% when treated against dental pulp stem cells. We conclude that gelatin-based hydrogels can be used as an alternative to conventional tissue adhesives.